How Experiences of Displacement and Resettlement Impact Health and Health Care Access for Resettled Rohingya Refugees: An Emic Perspective - Diane Barker Mitschke; Katherine Kitchens; Mohamad Faizal (Social Sciences, 2026)
This qualitative descriptive study uses an emic perspective to examine how displacement, statelessness, and resettlement shape health and health care access among 21 Rohingya people with refugee backgrounds living in the United States. Semi-structured interviews were conducted by a Rohingya member of the research team and analyzed using a taxonomic approach. Findings show that participants’ health concerns were not limited to general barriers commonly reported across refugee populations; rather, chronic pain, somaticized distress, comorbid conditions, and difficulties communicating health concepts emerged within a specific context of protracted statelessness, trauma exposure, limited Rohingya-language medical interpretation, and post-resettlement stress pile-up. Participants also described financial, transportation, and language barriers to health care access, alongside instances of positive, respectful care experiences. The study contributes to the literature by demonstrating how Rohingya participants describe health and care access through culturally and historically situated narratives, highlighting the need for trauma-informed, language-accessible, and culturally responsive health systems that attend to both structural barriers and embodied expressions of displacement.